Complications of Laparoscopic and Robotic Urologic Surgery - Ghavamian, Reza.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
There has been a huge rise in minimally invasive surgery (MIS) in urology. This has led to an urgent need for a textbook specifically dedicated to the issues and complications arising from laparoscopic and robotic procedures. With contributions from recognized urologic experts in MIS, Complications of Laparoscopic and Robotic Urologic Surgery fills this need by familiarizing the modern urologist with the common and the more eccentric complications of laparoscopic and robotic urologic surgery. Brief descriptions of the procedures are provided, as well as in-depth discussions of the diagnosis and management of complications associated with that particular prodecure. The book is divided into three specific sections. The first section covers medical and general considerations. The second section provides a generalized discussion of common surgical complications. Complications specific to robotic surgery in general are emphasized in a separate chapter. The third section is dedicated to procedure specific complications. Complications of upper tract and lower tract laparoscopic and robotic procedures are discussed in different sub-sections. Ample illustrations and images are provided throughout the text. This unique volume will be of great value to the practicing urologist adept at performing laparoscopy and robotics, the urologist training in these areas, and most importantly, residents in urology.
General and Medical Considerations -- Physiology of Laparoscopy and Pneumoperitoneum -- Anesthesia and Management of Anesthetic Complications of Laparoscopic Urological Surgery -- Metabolic and Renal Complications and Immunologic Implications of Laparoscopic Urologic Surgery -- Positional and Neuromuscular Complications of Laparoscopic and Robotic Urologic Surgery -- Surgical Complications -- Vascular Complications in Laparoscopic and Robotic Urologic Surgery -- Urinary and Urologic Complications of Laparoscopic and Robotic Urologic Procedures -- Visceral and Gastrointestinal Complications of Laparoscopic and Robotic Urologic Surgery -- Complications of Robotic-Assisted Laparoscopic Surgery: Iatrogenic and Doulogenic -- Procedure-Specific Complications -- Complications of Laparoscopic and Robotic Adrenal Surgery -- Complications of Laparoscopic Radical Nephrectomy and Nephroureterectomy -- Complications of Laparoscopic Donor Nephrectomy -- Complications of Laparoscopic Partial Nephrectomy -- Complications of Robotic Partial Nephrectomy -- Complications of Laparoscopic Retroperitoneal Lymph Node Dissection -- Complications of Laparoscopic and Robotic Pyeloplasty -- Complications of Laparoscopic and Robotic Ureteral Surgery -- Complications of Robotic Prostatectomy -- Methods and Maneuvers for Improving Functional Outcomes During Robotic Radical Prostatectomy -- Complications of Laparoscopic and Robotic-Assisted Radical Cystectomy -- Complications of Laparoscopic and Robotic Reconstructive Procedures for Urinary Incontinence and Pelvic Organ Prolapse -- Complications of Single Port Laparoscopic and Robotic Surgery -- Complications of Ablative Renal Procedures -- Complications of Laparoscopic and Robotic Pediatric Urologic Surgery -- Medicolegal Aspects of Minimally Invasive Urologic Surgery.
Keywords: Medicine; Surgery; Abdomen -- Surgery; Endoscopic surgery; Urology; Medicine & Public Health; Urology/Andrology.; Minimally Invasive Surgery; Abdominal Surgery; Surgery